Mortality among people who have experienced homelessness: protocol for a systematic review and meta-analysis - Rohan Borschmann; George C Patton; Stuart A Kinner; Susan M Sawyer; Jesse Young; Jessica Heerde (BMJ Open, 2023)
Introduction Homelessness is a major contributor to health inequalities. People who experience homelessness are at markedly increased risk of multiple and complex health morbidities which likely increase their susceptibility to early, preventable death. Despite this, the mortality burden in this group remains poorly understood, limited in part by insufficient synthesis of data at a global level. This systematic review will synthesise international literature examining rates of risk and protective factors for mortality among people who have experienced homelessness.Methods and analysis We will search MEDLINE, PsycINFO, Embase and PubMed for peer-reviewed cohort studies examining mortality among people who have experienced homelessness. No study eligibility restrictions will be placed on the date, country of origin, or language of publications, or age of the sample. We will assess the quality of included studies using the Methodological Standards for Epidemiological Research scale. Our measures of mortality will include: (A) incidence—all cause and cause specific, expressed as a crude mortality rate (CMR) per 1000 person-years, with 95% CI and (B) all cause and cause specific, indirectly standardised mortality ratios (SMRs) with 95%CI. Associations between risk and protective factors and all-cause and cause-specific mortality will be reported using pooled relative risk ratios with 95% CI. Where there are sufficient data, the influence of subgroup and methodological factors on CMRs, SMRs and predictive factors will be examined using meta-regression.Ethics and dissemination This study does not require institutional ethics review or approval as it will synthesise findings from published studies that have previously been granted relevant ethics approvals. Study findings will be disseminated through a peer-reviewed journal article, conference and seminar presentations. A plain language summary will be distributed through the authors’ academic and professional networks.PROSPERO registration number CRD42021272937.